Hippo pathway monomerizes STAT3 to regulate prostate cancer growth. Issue 8 (28th June 2022) - Tang, Qingfeng; Fang, Jing; Lai, Weiqi; Hu, Yu; Liu, Chengwan; Hu, Xiaobo; Song, Caiyong; Cheng, Tianmu; Liu, Rui; Huang, Xiaoke
Abstract: Prostate cancer ranks among the most commonly diagnosed malignancies for men and has become a non‐negligible threat for public health. Interplay between inflammatory factors and cancer cells renders inflammatory tissue environment as a predisposing condition for cancer development. The Hippo pathway is a conserved signaling pathway across multiple species during evolution that regulates tissue homeostasis and organ development. Nevertheless, whether Hippo pathway regulates cancer‐related inflammatory factors remains elusive. Here, we show that high cell density–mediated activation of the Hippo pathway blunts STAT3 activity in prostate cancer cells. Hippo pathway component MST2 kinase phosphorylates STAT3 at T622, which is located in the SH2 domain of STAT3. This phosphorylation blocks the SH2 domain in one STAT3 molecule to bind with the phosphorylated Y705 site in another STAT3 molecule, which further counteracts IL6‐induced STAT3 dimerization and activation. Expression of a nonphosphorylatable STAT3 T622A mutant enhances STAT3 activity and IL6 expression at high cell density and promotes tumor growth in a mice xenograft model. Our findings demonstrate that STAT3 is a novel phosphorylation substrate for MST2 and thereby highlight a regulatory cascade underlying the crosstalk between inflammation and the Hippo pathway in prostate cancer cells. Abstract : When Hippo pathway is activated at high cell density, MST2 phosphorylates STAT3 at T622, which inhibits STAT3 dimerization and activation. STAT3 T622 phosphorylation further impedes prostate cancer growth, and is associated with better prostate cancer outcome.